Heart failure in systemic right ventricle: Mechanisms and therapeutic options - Sabbah, Belal Nedal; Arabi, Tarek Ziad; Shafqat, Areez; Abdul Rab, Saleha; Razak, Adhil; Albert-Brotons, Dimpna Calila (Frontiers in Cardiovascular Medicine, 2023)
Systemic right ventricle (sRV) is seen in congenital heart diseases, such as D-transposition of the great arteries (d-TGA) and congenitally corrected-transposition of the great arteries (cc-TGA). Usually working against a low-pressure low-resistance pulmonary circulation, the sRV undergoes adaptations to act as the systemic pump against the high afterload of the systemic circulation. These changes chronically result in decompensation and consequent heart failure. Many cc-TGA patients and d-TGA patients with previous atrial switch repair suffer from heart failure, a significant long-term cause of morbidity, mortality, and health expenditures. Hence, identifying novel biomarkers and therapeutic targets may enhance clinical care to the benefit of sRV patients, heart failure patients, and the healthcare system. This review discusses the mechanisms and mediators of heart failure in sRV patients with biventricular circulation and how these mediators may be targeted clinically to alleviate sRV failure.